Transformation dependence of lead zirconate titanate (PZT) as shown by PiezoAFM surface mapping of Sol-gel produced PZT on various substrates - Dunn, Steve; Whatmore, Roger W. (Taylor and Francis, 2001)
PZT was grown on STP (Si/SiO2/Ti/Pt (Ti 5nm, Pt 100nm)), SAP (Si/Si3N4/Al/Ti/Pt (Al 100nm, Ti 10nm, Pt 15nm)) and GI (Glass/ITO(Indium Tin Oxide)). In each case the PZT underwent the same heat treatment, 200ºC for 2 minutes and then 530ºC for 5 minutes. The extent of perovskite formation was evaluated using Piezoresponse force microscopy (PFM). This provided information about the domain orientation and spatial distribution of ferroelectric material in the PZT film. This showed that PZT/STP underwent complete transformation to the perovskite phase. However, for the PZT/SAP and GI incomplete transformation to the perovskite occurred. A system of rosettes surrounded by an amorphous matrix developed. The size and density of the PZT rosettes on the surface was found to be substrate dependent. For Gi/PZT the density of rosettes formation is ca. 1/μm2, compared to 4/μm2 for PZT/SAP. The rosettes for the PZT on GI grow a maximum size of 2μm, which compares to 1μm for PZT on SAP. Differences in the observed growth rate and nucleation density are associated with the back electrode stability and crystal structure, effects that will be discussed in this paper.
Keywords: piezoresponse force microsopy; nucleation; PZT; ferroelectric domains